High plasma efavirenz level and CYP2B6*6 are associated with efavirenz-based HAART-induced liver injury in the treatment of naïve HIV patients from Ethiopia: a prospective cohort study - Yimer, Getnet; Haefeli, Walter E.; Burhenne, Jürgen (The pharmacogenomics journal, 2012)
The objective of this study was to assess the incidence, timing and identify pharmacogenetic, efavirenz (EFV) pharmacokinetic and biochemical predictors of EFV-based antiretroviral therapy (ART) drug-induced liver injury (DILI). ART-naïve HIV patients (n=285) were prospectively enrolled. Pretreatment laboratory evaluations included hepatitis B surface antigen and C antibody, CD4 count and viral load. Liver tests were done at baseline, 1st, 2nd, 4th, 8th, 12th, 24th and 48th weeks during ART. Plasma EFV and 8-hydroxyefvairenz concentration was determined at week 4 using liquid chromatography-mass spectrometry. CYP2B6, CYP3A5, ABCB1 3435C/T and UGT2B7*2 genotyping was done using Taqman genotyping assay. Data were analyzed using survival analysis and Cox proportional hazards model. The incidence of DILI was 15.7% or 27.9 per 100 person-years and that of severe injury was 3.4% or 6.13 per 100 person-years. The median time for the development of DILI and severe injury was 2 and 4 weeks after initiation of ART, respectively. There was significant association of DILI with lower baseline platelet, albumin, log plasma viral load and CD4 count (P=0.031, 0.037, 0.06 and 0.019, respectively). Elevated baseline alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, plasma EFV level and CYP2B6*6 were good predictors for the development of DILI (P=0.03, 0.01, 0.016, 0.017 and 0.04, respectively). We report for the first time CYP2B6*6 as a putative genetic marker and high plasma EFV concentration as intermediate biomarker for vulnerability to EFV-induced liver injury in HIV patients. CYP2B6 genotyping and/or regular monitoring of EFV and lever enzymes level during early therapy is advised for early diagnosis and management of DILI.